High-fat diet stimulates the gut pathogenic microbiota and maintains hepatic injury in antibiotic-treated rats - Al-Daihan, Sooad; Ben Bacha, Abir; Al-Dbass, Abeer M; Alonazi, Mona Awad; Bhat, Ramesa Shafi (Cellular and Molecular Biology, 2018)
The gut and the liver are closely linked to each other, as changes in the gut microbiota can play a significant role in the development of many liver diseases. Gut bacteria respond rapidly to changes in diet and thus can affect the liver through their metabolites. The impact of a high lipid diet on the liver in the presence of an altered gut flora modulated by ampicillin was investigated. The study was performed on 30 male Western albino rats randomly divided into 3 groups: control (phosphate buffered saline treated), group II (ampicillin 50 mg/kg for three weeks to induce microbiota alterations and fed on standard diet) and group III (same dose of ampicillin and fed on a lipid rich diet). Stool samples were collected for qualitative determination of bacteria. Serum hepato-specific markers, in addition to Glutathione (GSH), Lipid peroxidase (MDA), Glutathione-S- transferase(GST), and vitamin C in liver tissues, were measured. Altered gut microbiota significantly increased the level of the hepato-specific marker MDA and reduced the GST, GSH and vitamin C levels. However, animals fed a lipid rich diet displayed a more significant shift in hepatic markers and antioxidants. Moreover, a new switch in composition of the gut bacteria was observed by feeding the lipid rich diet. Our study showed that bacterial overgrowth in the gut can be associated with liver dysfunction and that a high lipid diet can promote the overgrowth of some liver damaging microflora during antibiotic treatment.